2018
DOI: 10.4067/s0718-95162018005000201
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of rice-residue biochar and N-fertilizer on soil functions and crop biomass in contrasting soils

Abstract: There is limited understanding of the effects of rice residue biochar, particularly when applied in combination with nitrogen (N) fertilizer on soil fertility, soil C sequestration and crop productivity. A one-year pot experiment was established to examine effects of rice residue biochar (0, 10, 20 and 40 t ha -1 ) and N (0, 60, 90, 120 and 150 kg N ha -1 ) in soils with contrasting texture (loamy sand and sandy clay loam) in a wheat-maize cropping sequence. Biochar was only applied once before sowing wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…They reported that application of rice straw biochar produced at a low temperature (300°C) decreased soil pH (from 7.88 to 7.72), while biochar made at a higher temperature (400 and 500°C) had no significant effect on soil pH. A similar increase in soil pH was reported by Singh Mavi et al (2018) where rice-residue Fig. 3 Cation exchange capacity (CEC), pH, total organic carbon (TOC), dissolved organic carbon (DOC), and microbial biomass carbon (MBC) in different biochar treatments at 1 and 2% of application rate.…”
Section: Soil Ph and Cecsupporting
confidence: 59%
See 1 more Smart Citation
“…They reported that application of rice straw biochar produced at a low temperature (300°C) decreased soil pH (from 7.88 to 7.72), while biochar made at a higher temperature (400 and 500°C) had no significant effect on soil pH. A similar increase in soil pH was reported by Singh Mavi et al (2018) where rice-residue Fig. 3 Cation exchange capacity (CEC), pH, total organic carbon (TOC), dissolved organic carbon (DOC), and microbial biomass carbon (MBC) in different biochar treatments at 1 and 2% of application rate.…”
Section: Soil Ph and Cecsupporting
confidence: 59%
“…Therefore, the increase in soil MBC could be a consequence of biochar addition. The addition of B200 showed higher microbial biomass probably due to the presence of the more volatile matter (Table 3) which are easily decomposable organic substances and available for microbial utilization (Liang et al 2016;Khadem and Raiesi 2017;Singh Mavi et al 2018). In contrast, increasing the pyrolysis temperature could lower MBC, probably due to the lower volatile matter in biochar and higher aromaticity (Table 3).…”
Section: Soil Toc Doc and Mbcmentioning
confidence: 99%
“…Cornelissen et al (2013) reported that BC application to maize plants exposed to drought stress triggered the increased nutrient retention in growth media with variable physical/chemical characteristics. Also, in soils with contrasting texture (loamy sand and sandy clay loam), maize had the beneficial effects of biochar on biomass (Singh Mavi et al 2018). Therefore, as well as trials in the soil environment, there might be an interaction between nutrient mobility and BC in hydroponic culture.…”
Section: Discussionmentioning
confidence: 99%
“…in biochar (Inyang et al 2016). Thanks to functional groups, in soils treated with biochar, it has influenced the physicochemical properties including soil pH and water holding capacity, and aeration, soil biological activity, and aggregate stability (Bamminger et al 2016;Singh Mavi et al 2018). Besides, under stress conditions (such as water, drought, and salt stress), there is an improvement on photosynthetic apparatus, water-use efficiency, and crop productivity in BC-applied plants such as tomato, maize, and milk thistle (Akhtar et al 2014;Haider et al 2015;Keshavarz Afshar et al 2016;Paneque et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar helps to improve the soil physical, chemical, and biological properties. Soil pH, electrical conductivity (EC), cation exchange capacity (CEC), organic carbon content (OC), and available nutrients (NPK) are significantly increased with different application rates of biochar (Nzediegwu et al 2019;Singh et al 2018). Biochar is a cost-effective or cheaper organic fertilizer as compared to other inorganic fertilizers (William and Qureshi 2015).…”
Section: Introductionmentioning
confidence: 99%